PEMBUATAN BROWNIES TEMPE SEBAGAI MAKANAN SEHAT GUNA MENINGKATKAN GIZI PADA ANAK DAN IBU HAMIL DESA BATU NAMPAR - Nabila, Siti Maulidiya; Rasyd, Anwar; Prastuti, Aulia Widya; Jauhari, M. Abim; Al-Aqsha, L. Moh. Riri Rivari; Atman, B. Eggy Tamara; Susanti, Sri; Sari, Nilam; Maenarni, Lilis; Agustin, Melly (Universitas Mataram, 2023)
Batu Napar Village is in the Jerowaru District, East Lombok Regency, West Nusa Tenggara Province. Tempe is a typical Indonesian food made from soybeans. Tempe is a healthy food because it contains various nutrients needed by the body. Tempe has many ingredients such as phosphorus, iron, vitamins B, C, and also anti-oxidants. In Batu Napar Village there are children with cases of stunting and malnutrition. Therefore, the Unram KKNT together with the Batu Napar Village PKK and Posyandu cadres made an innovation in the form of processing tempeh into tempeh brownies as an effort to fulfill nutrition for children and pregnant women through making healthy food. This healthy food counseling and demonstration activity received a very positive response from the community. Many people feel helped by this activity.